SARC009: Phase 2 study of dasatinib in patients with previously treated, high‐grade, advanced sarcoma. Issue 6 (28th December 2015) - Schuetze, Scott M.; Wathen, J. Kyle; Lucas, David R.; Choy, Edwin; Samuels, Brian L.; Staddon, Arthur P.; Ganjoo, Kristen N.; von Mehren, Margaret; Chow, Warren A.; Loeb, David M.; Tawbi, Hussein A.; Rushing, Daniel A.; et al.
Abstract : BACKGROUND: Dasatinib exhibited activity in preclinical models of sarcoma. The Sarcoma Alliance for Research through Collaboration (SARC) conducted a multicenter, phase 2 trial of dasatinib in patients with advanced sarcoma. METHODS: Patients received dasatinib twice daily. The primary objective was to estimate the clinical benefit rate (CBR) (complete response or partial response within 6 months or stable disease duration of ≥6 months) with a target of ≥25%. Patients were enrolled into 1 of 7 different cohorts and assessed by imaging every 8 weeks using Choi criteria tumor response and a Bayesian hierarchical design. For each subtype, enrollment was stopped after a minimum of 9 patients were treated if there was a <1% chance the CBR was ≥25%. RESULTS: A total of 200 patients were enrolled. Accrual was stopped early in 5 cohorts because of low CBR. The leiomyosarcoma (LMS) and undifferentiated pleomorphic sarcoma (UPS) cohorts fully accrued and 6 of 47 and 8 of 42 evaluable patients, respectively, exhibited clinical benefit. The probability that the CBR was ≥25% in the LMS and UPS cohorts was 0.008 and 0.10, respectively. The median progression‐free survival ranged from 0.9 months in patients with rhabdomyosarcoma to 2.2 months in patients with LMS. The median overall survival was 8.6 months. The most frequent adverse events were constitutional, gastrointestinal, and respiratory, and 36% of patients required dose reduction for toxicity. Serious adverse events attributed to therapy occurred in 11% of patients. CONCLUSIONS: Dasatinib may have activity in patients with UPS but is inactive as a single agent in the other sarcoma subtypes included herein. The Bayesian design allowed for the early termination of accrual in 5 subtypes because of lack of drug activity. Cancer 2016;122:868–74 . © 2015 American Cancer Society . Abstract : Dasatinib, an inhibitor of multiple tyrosine kinases, was evaluated for anticancer activity in distinct histologic subtypes of sarcoma. Use of an adaptive Bayesian design allowed for the efficient estimation of clinical benefit from dasatinib and limited enrollment in subtypes in which no activity was observed.